Identification of factors that influence the delivery fee pricing of on-demand delivery services - De Oliveira, Leise Kelli; Mello, Carine Aragão de; Carneiro, Cheyenne Mariana de Oliveira; Costa, Tatiane Eugênia Remígio da; Araújo, Gracielle Gonçalves Ferreira de; Maia, Maria Leonor Alves (Frontiers in Future Transportation, 2022)
The on-demand delivery service has increased in Brazil during the COVID-19 pandemic, mainly by requesting ready meals. However, while consumers appreciate the convenience, the delivery fee is a decisive factor in the purchase process. However, the delivery fee pricing strategy of an on-demand delivery service platform is unknown in the literature. Thus, this paper aims to analyze the factors that influence the delivery fee pricing of on-demand delivery services and explores the impact of delivery fee strategies on the remuneration of couriers. We collected data from the three leading on-demand delivery services platforms regarding the product type, order price, service fee, delivery fee, order day, order time, waiting time, and distance. The database comprises 1,440 orders in 12 Brazilian municipalities. A linear regression model was estimated to identify the factors influencing the delivery fee pricing considering different product types. Findings showed that product type has a diverse effect on delivery fee pricing. Moreover, distance, regardless the product type, positively influences the delivery fee. The delivery fee of the ready meals is affected by the service fee, waiting time, order day, and order time. Furthermore, waiting time and order day affect the delivery fee of supermarket and bakery products and beverages. Finally, the delivery fee of medicine products is influenced by order day and time. Findings can be helpful for the pricing strategy of on-demand services.